Exploration on the Mechanism of Ubiquitin Proteasome System in Cerebral Stroke - Li, Yu-Chao; Wang, Yan; Zou, Wei (Frontiers in Aging Neuroscience, 2022)
Stroke's secondary damagee, such as inflammation, oxidative stress, and mitochondrial dysfunction, are thought to be crucial factors in the disease's progression. Despite the fact that there are numerous treatments for secondary damage following stroke, such as antiplatelet therapy, anticoagulant therapy, surgery, and so on, the results are disappointing and the side effects are numerous. It is critical to develop novel and effective strategies for improving patient prognosis. The UPS (ubiquitin proteasome system) is the hub for the processing and metabolism of a wide range of functional regulatory proteins in cells. It is critical for the maintenance of cell homeostasis. With the advancement of UPS research in recent years, it has been discovered that UPS is engaged in a variety of physiological and pathological processes in the human body. UPS is expected to play a role in the onset and progression of stroke via multiple targets and pathways. This paper explores the method by which UPS participates in the linked pathogenic process following stroke, in order to give a theoretical foundation for further research into UPS and stroke treatment.